DENTAL CARIES AND PARENTS' KNOWLEDGE LEVEL IN MAINTAINING CHILDREN'S DENTAL HEALTH THROUGH TELESURVEY IN CIMAHI - Rina Putri Noer Fadilah; Joane Rante Arung; Novia Septiani; Intan Wijayathi; Tania Syifomade; Sheila Syahdania (Fakultas Kedokteran Gigi Unjani, 2021)
Dental caries is the most common dental disease suffered by the Indonesian population, especially elementary school children—an oral dental condition caused by various factors, including children's lack of parental knowledge. The existence of a government program through the UKGS requires screening for every child in elementary school. The Covid-19 pandemic has hampered the screening process in elementary schools because students study online at home. This study aims to conduct a telesurvey of dental caries in children and determine parents' knowledge in maintaining the health of children's oral teeth. The cross-sectional method and the questionnaire were used in this study as a measuring tool. Furthermore, dental examinations are carried out using a gadget/mobile phone uploaded to the google form. The analysis used in this study is the univariate method. The results showed that 340 elementary school students at Padasuka Health Center had the primary teeth' caries index in the medium category. The caries index of the permanent teeth was in the deficient class. The prevalence of caries in elementary school students at Padasuka Health Center is 80%. At the same time, parental awareness regarding the maintenance of children's oral health is considered in the high category. The telesurvey conducted on elementary school students at Padasuka Health Center was used as an illustration to determine the status of oral health, particularly dental caries. Hopefully, the telesurvey will make it easier for respondents and health workers to assess oral health. DOI : 10.54052/jhds.v1n2.p131-141